Pengembangan Sistem Informasi Keterbukaan Desa (SiKD) Menggunakan Metode Spiral Berbasis Website - Bayu Widodo; Uding Sastrawan; Gema Parasti Mindara; Wien Kuntari; Budi, Budi (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2024)
The development of the Village Openness Information System (SiKD) aims to encourage transparency and community participation in managing village government. This research highlights the importance of using information technology in improving the performance of village governments, especially in Mekarsari Village (Sukabumi), Garumukti Village (Garut), and Bantar Kulon Village (Pekalongan). These three villages have mountainous geographical characteristics and limited transportation access, but have great potential in the agricultural sector. The research methodology uses the Spiral Model which involves the stages of problem identification, planning, risk analysis, engineering, construction and release, and user evaluation. Data collection was carried out through observation and interviews with village officials and community leaders. The research results show that the development of SiKD with the Spiral Model allows the preparation of detailed and systematic digital data, which is presented in the form of a dashboard. The SiKD dashboard facilitates measurable and sustainable village development planning, focuses on utilizing village funds according to residents' needs, and accelerates the achievement of Sustainable Development Goals (SDGs). The implementation of SiKD is expected to increase information transparency and the performance of village government services effectively and efficiently.